Development of Marker-Free Insect-Resistant Indica Rice by Agrobacterium tumefaciens-Mediated Co-transformation - Ling, Fei; Zhou, Fei; Chen, Hao; Lin, Yongjun (Frontiers in Plant Science, 2016)
Agrobacterium-mediated co-transformation is an efficient strategy to generate marker-free transgenic plants. In this study, the vectors pMF-2A* containing a synthetic cry2A* gene driven by maize ubiquitin promoter and pCAMBIA1301 harboring hygromycin phosphotransferase gene (hpt) were introduced into Minghui86 (Oryza sativa L. ssp. indica), an elite indica restorer line. Two independent transformants containing both the cry2A* gene and hpt gene were regenerated. Several homozygous marker-free transgenic progenies were derived from family 2AH2, and three of them were selected for further insect bioassay in the laboratory and field. Insect-resistance assays revealed that all the three transgenic lines were highly resistant to striped stem borer (Chilo suppressalis), yellow stem borer (Tryporyza incertulas) and rice leaf folder (Cnaphalocrocis medinalis). The measurement of Cry2A protein concentration showed that Cry2A protein was stably expressed in leaves and stems of homozygous transgenic lines and their hybrids. The yields of the marker-free homozygous transgenic lines and their hybrids were not significantly different from those of their corresponding controls. Furthermore, the results of flanking sequence isolation showed that the T-DNA in line 8-30 was integrated into the intergenic region of chromosome 2 (between Os02g43680 and Os02g43690). These results indicate that the marker-free transgenic rice has the potential for commercial production.